Clinical presentation and outcomes of hospitalized children with COVID‐19 in Mexico City. Issue 12 (14th September 2022) - Diaz, David R.; Urrutia, Samuel; Gutierrez, Gabriel; Cuevas, Francisco
Abstract: We describe the demographic, clinical, radiological, and laboratory findings relating them also to the severity and clinical outcome of 129 children (0–18 years) who were admitted to a tertiary care pediatric hospital in Mexico City due to severe acute respiratory syndrome coronavirus 2 infection between April 1, 2020 and March 31, 2021. The infection was confirmed using reverse transcription‐polymerase chain reaction Fever (82.2%), tachypnea (72.1%), and cough (71.3%) were the most reported signs at the moment of hospitalization. The most frequent radiological pattern that stood out was the interstitial pattern (66.7%). History of oncologic pathology (25.6%) was the most frequent past medical history. Non‐steroidal anti‐inflammatory drugs (93%), antibiotics (57.4%), and steroids (40.3%) were the most common medication given. The average hospitalization stay was 14.2 days, and 21.7% of the total patients required transfer to the intensive care unit. At discharge, 20.2% required oxygen on an outpatient basis, and unfortunately, 7.0% of the patients who were admitted to the institute for COVID‐19 died. Our findings confirm that COVID‐19 in children has a mild presentation except for patients with hematologic/oncologic comorbidities who had severe presentations.